2005
DOI: 10.1021/la0512345
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Induced Generation of Small Silver Particles in SPEEK/PVA Polymer Films and Solutions:  UV−Vis, EPR, and FT-IR Studies

Abstract: The present study is centered on the processes involved in the photochemical generation of nanometer-sized Ag particles via illumination at 350 nm of aqueous solutions and cross linked films containing sulfonated poly(ether ether ketone) and poly(vinyl alcohol). Optical and electron paramagnetic resonance experiments, including electron nuclear double resonance data, proved conclusively that the photogenerated chromophore exhibiting a band with lambda(max) = 565 nm is an alpha-hydroxy aromatic (ketyl) radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 58 publications
4
45
0
Order By: Relevance
“…Alexandrov et al 9 reported the diffusion coefficient (D) of gold atoms in PMMA matrix at 348 K as 2 × 10 -7 cm 2 s -1 , which is quite large compared to other reports about diffusion of metal atoms in polymers. For example, in a detailed paper about diffusion of metal atoms in polymers by Faupel et al, 10 the corresponding diffusion coefficients are given for gold atoms in different polymer matrices (like BPA-PC and TMC-PC) at temperatures about 500 K. These reported values are in the range of 10 , smaller by about 7 orders of magnitude. In contrast to several studies on metal atoms, no corresponding reports are available dealing with diffusion of metal ions (i.e., AuCl 4 -) in polymer matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Alexandrov et al 9 reported the diffusion coefficient (D) of gold atoms in PMMA matrix at 348 K as 2 × 10 -7 cm 2 s -1 , which is quite large compared to other reports about diffusion of metal atoms in polymers. For example, in a detailed paper about diffusion of metal atoms in polymers by Faupel et al, 10 the corresponding diffusion coefficients are given for gold atoms in different polymer matrices (like BPA-PC and TMC-PC) at temperatures about 500 K. These reported values are in the range of 10 , smaller by about 7 orders of magnitude. In contrast to several studies on metal atoms, no corresponding reports are available dealing with diffusion of metal ions (i.e., AuCl 4 -) in polymer matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of silver nanoparticles in PVA polymer matrix could provide antibacterial activity, which is highly desirable in medical field. Various methods including solvent evaporation, electron radiation, UV light, thermal annealing, and in situ chemical reduction have been proposed for the synthesis of materials based on PVA/silver nanoparticles [17][18][19][20][21][22][23][24][25][26][27][28] which yields different morphology and sizes of silver depending on the preparation method. PVA is very sensitive towards moisture and as a result reduces the film strength [16] that is highly undesirable of the films used for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the antibacterial functions of PVA/BP films are due to formation of triplet radicals and potential production of H 2 O 2 . Photoirradiated BP is well known to attract H atoms from suitable hydrogen donors such as amines or alcohol (i.e., PVA) and form corresponding benzophenone ketyl (BPK) radicals 22. And when exposed to oxygen, the BPK radicals rapidly reoxidize to form BP with an accompanying formation of H 2 O 2 22, 23.…”
Section: Resultsmentioning
confidence: 99%